Feasibility study on the combination of limestone and gravel for the use in surface wearing course - Kelvin Sim Kai, Tung (Universiti Malaysia Sarawak (UNIMAS), 2019)
The increasing shortage of quality aggregate material for pavement construction is one of the major problems in Sarawak. Moreover, there are large quantity of substandard material such as limestone available in all part of Sarawak which can be potentially use as wearing course and to reduce the dependability of using quality aggregates such as granite to produce a more economical as well as sustainable pavement. In this study, the possibility of improving limestone bituminous mix was investigated by performing several replacements with granite aggregate. The optimum mix proportion by using full limestone was determined and known as unmodified bituminous mix. The replacements include fully limestone replacement, fully coarse limestone aggregate replacement with fully fine granite aggregate, and fully fine limestone aggregate replacement with coarse granite aggregate. The results showed that both fully fine limestone replacement with coarse granite aggregate and the optimum bitumen content (OBC) for fully limestone mix comply with JKR standard specification (2008).